Impact of Accounting Records Keeping On the Financial Performance of Small Scale Enterprises:a Case Study of Selected Smes in Mukono District - Stellah Kirabo Namugumya (Uganda Christian University, 2024)
This research dissertation gives an experience I had during my research period at Uganda Christian University. The executive summary gives a summary of what the dissertation is all about. Chapter one of the research dissertation generally shows the introduction of the study, the background of the study, problem statement, objectives, and scope of the study and the significance of the study. Chapter two mainly looks at the literature review where it focuses on the introduction, overview of the main concepts, empirical review of the specific objectives in detail i.e. the most common accounting record practices used by small scale enterprises, the most common accounting record challenges faced by small scale enterprises and the relationship between the accounting record keeping and financial performance of small scale enterprises in Mukono district. Chapter three looks at the research methodology where it introduces it. It also looks at the research design, population of the study, data sources, research instruments i.e. questionnaires, interviews and observations then also continues to look at the measurement of variables, data collection procedures, ethical consideration and then limitation of the study. Chapter four then talks about presentation analysis and interpretation of the results obtained from the respondents during the study. It goes ahead to introduce it then talks about the profile of the respondents i.e. age, gender. Lastly, chapter five gives the summary on each objectives, conclusion and then recommendations. My remarks on the finding are given in the conclusion I also gave recommendations how to overcome and improve on the identified problem in the study.